Decision Support System in Determining the right Investment Instrument - Gunawan, Dedi (Jurnal Transformatika, 2025)
The number of investment instrument is often confusing for people who have minimal knowledge but still want to investing. Due to the many investments instrument offered, with the lack of public literacy in financial management, most people have a fear of missing out which case the phenomena of FOMO (Fear of Missing Out), the desire of people to get rich quick without thinking about the risk future which result in many fraudulent practices circulating in the community. This study aims to assist users in deciding the right investment instrument according to the user s risk profile. The decision support system in determining investment instrument with AHP (Analytical Hierarchy Process) Method is a method for problems in determining priorities from various alternative. AHP will make it easier to determine the right instrument.